Makhana (Euryale ferox Salisb.): Possibilities for cultivation in Haryana (IASH Indian Journal of Arid Horticulture, 2026)
Makhana (Euryale ferox Salisb.) was cultivated at the Botanical Garden, CCS HAU, Hisar during 2022–23 to evaluate its cultivation potential under Haryana conditions. Seeds were sown in October 2022 in puddled clay soil at a depth of 4–5 cm in a water tank containing a 10 cm soil layer. Seedlings emerged approximately one month after sowing, with initial leaves exhibiting a reddish-purple coloration and triangular shape. Plant growth remained slow during the winter months due to low temperature stress, but accelerated from March onwards, producing large, round, spiny leaves. Vegetative growth continued until September, followed by flowering from October 2023 to January 2024. Flowering, seed set, maturation, and seed dispersal occurred simultaneously on different shoots. The seed yield ranged from 50 to 100 g per plant.